The role of mother–child and teacher–child relationship on academic achievement. Issue 2 (4th March 2017) - Caputi, Marcella; Lecce, Serena; Pagnin, Adriano
Abstract: Robust findings have highlighted the importance of early cognitive abilities for academic performance. However, little is known about the role played by relational variables. In this longitudinal study, we examined children's relationship with their mothers and teachers as predictors of later academic achievement. We addressed this issue following a group of 45 Italian children (29 boys) from the last year of preschool (mean age: five years and six months) until Year 4 of primary school (mean age: nine years and six months). Results showed that mother–child relationship at age 5 and teacher–child relationship at age 7 correlate with children's academic achievement at age 9, controlling for early background and verbal abilities. Further analyses showed that teacher–child conflict partially mediates the relationship between early mother–child conflict and children's later academic achievement. Mechanisms by which relational variables influence learning outcomes are discussed.